Numerical investigation of heat transfer and fluid motion in air inflatable textiles: Effect of thickness, surface emissivity and ambient temperature. (November 2022) - Tu, Lexi; Zhang, Huimin; Wang, Jilong; Sun, Jiahui; Xu, Guangbiao; Wang, Fumei; Shen, Hua
Abstract: Air inflatable textile has attracted increasing attention due to the advantage of light, cheap, environmentally friendly and low thermal conductivity. While its thermal insulation is still not yet well understood since the complex interior heat and mass transfer under various thickness and ambient conditions. In this work, a three-dimensional model was developed to investigate the fluid motion and heat transfer in both air inflatable and fiber-filled textiles. The coupled conduction, convection and radiation were modelled by CFD approach. The experimental and numerical results were compared to verify the proposed model. Good agreements were found with the average difference in surface temperature and heat flux less than 2.54% and 9.95%, respectively. Then the effect of various parameters including thickness, surface emissivity and ambient temperature on heat flux, thermal resistance and fluid flow behavior was further analyzed. The simulated interior velocity and temperature distribution suggested that the higher thickness (≥10 mm) was not favorable for better thermal insulation when the air was adopted as thermal insulation layer. Because more available space for air movement would accelerate thermal convection and result in the deteriorated thermal insulation. In addition, inner surface layer with lower emissivity could effectively suppress the thermal radiation in air inflatable textiles and was beneficial to increase the thermal insulation. Besides, the thermal insulation of fiber-filled textile was nearly unaffected when lower ambient temperature was applied, while that of air inflatable textiles significantly decreased due to the aggravated convective heat and flow transfer under large temperature difference. Highlights: Thermal insulation of air inflatable and fiber-filled textiles was compared using CFD model. Coupled conduction, convection and radiation were simultaneously investigated. Fluid motion, development and growth of convection cells in air inflatable textiles were achieved. Radiative and convective contributions on total heat transfer were clarified. Effect of thickness, surface emissivity and ambient temperature on fluid flow behavior was analyzed.